2014
DOI: 10.1051/0004-6361/201423784
|View full text |Cite
|
Sign up to set email alerts
|

Probing X-ray burst – accretion disk interaction in low mass X-ray binaries through kilohertz quasiperiodic oscillations

Abstract: The intense radiation flux of Type I X-ray bursts is expected to interact with the accretion flow around neutron stars. High frequency quasiperiodic oscillations (kHz QPOs), observed at frequencies matching orbital frequencies at tens of gravitational radii, offer a unique probe of the innermost disk regions. In this paper, we follow the lower kHz QPOs, in response to Type I X-ray bursts, in two prototypical QPO sources, namely 4U 1636-536 and 4U 1608-522, as observed by the Proportional Counter Array of the R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…We performed time-resolved spectroscopy of the burst and the underlying accretion emission, where we allowed the latter to change in flux. Despite that the burst was not very long, bright, or energetic, we found that the accretion flux was enhanced by a factor of 5 during the peak of the X-ray burst and returned to its pre-burst level after 100 s. Such enhancements have been detected in a large number of bursts from many different sources, both during hard and soft X-ray spectral states, and both for PRE and non-PRE bursts (in 't Zand et al 2013;Worpel et al 2013Worpel et al , 2015Ji et al 2014aJi et al , 2015Peille et al 2014).…”
Section: Enhancement Of the Persistent Emissionmentioning
confidence: 52%
“…We performed time-resolved spectroscopy of the burst and the underlying accretion emission, where we allowed the latter to change in flux. Despite that the burst was not very long, bright, or energetic, we found that the accretion flux was enhanced by a factor of 5 during the peak of the X-ray burst and returned to its pre-burst level after 100 s. Such enhancements have been detected in a large number of bursts from many different sources, both during hard and soft X-ray spectral states, and both for PRE and non-PRE bursts (in 't Zand et al 2013;Worpel et al 2013Worpel et al , 2015Ji et al 2014aJi et al , 2015Peille et al 2014).…”
Section: Enhancement Of the Persistent Emissionmentioning
confidence: 52%
“…However, it is not yet clear if the simple method used by Worpel et al (2013) adequately captures the complexity of burst-disc interactions. Indeed, Peille et al (2014) recently argued that the presence of high frequency quasi-periodic oscillations (QPO) before and during the X-ray bursts, while fa is still above unity, is not consistent with this methodology: the high frequency QPOs are thought to be produced in the inner disc regions, but the high fa values imply that this region would be accreted onto the NS. However, this argument breaks down if the QPOs are associated with the spreading layer as suggested by the Fourier-frequency resolved spectra (Gilfanov et al 2003).…”
Section: Open Issuesmentioning
confidence: 99%
“…In principle, the accretion-powered emission could, at some times during a burst, be more luminous than before or after the burst, if the radiation from the burst significantly increases the radiation drag on the gas orbiting in the disk, causing the accretion rate to the stellar surface to increase, or it could be less luminous, when the increased radiation drag has depleted the inner disk. Unfortunately, the observed variations in the background are not understood theoretically and do not appear to be correlated with other properties of the bursts in any obvious way (see Peille et al 2014 and references therein). Consequently, whether the background varies during a particular burst, and if so, by how much and in which direction, cannot currently be predicted.…”
Section: Backgroundsmentioning
confidence: 99%
“…Independent knowledge of the background would improve the constraints on M and R eq derived by waveform-fitting (see Lo et al 2013), but both observational evidence (Yu et al 1999;Kuulkers et al 2003;Chen et al 2011;in't Zand et al 2011;Serino et al 2012;Degenaar et al 2013;Worpel et al 2013;Peille et al 2014) and theoretical arguments (Walker 1992;Miller & Lamb 1996;Ballantyne & Strohmayer 2004;Ballantyne & Everett 2005) indicate that the accretion-powered emission from neutron star systems is substantially different during a burst than before or after.…”
Section: Backgroundsmentioning
confidence: 99%